Analisis Risk Profile, Good Corporate Governance, Earning, Dan Capital Untuk Menilai Kesehatan Perusahaan: Analisis Risk Profile, Good Corporate Governance, Earning, Dan Capital Untuk Menilai Kesehatan Perusahaan - Pristiwantiyasih; Dwi Ermayanti Susilo (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
The monetary crisis that occurred in Indonesia in 1998 this crisis occurred due to the fall in the exchange rate of the rupiah against the dollar and liquidity problems, as a result of the occurrence of this monetary crisis caused huge state losses. With this incident, Bank Indonesia, as the bank that oversees bank regulations in Indonesia, stipulates that companies mus be able to assess the health level of their own companies using the RGEC (Risk Profile, Good Corporate Governance, Earning, dan Caiptal) methods. This study uses as purposive sampling method with 13 (thirteen) companies listed on the Indonesia Stock Exchange ini 2018 – 2020. In this study found 2 (two) companies that were categorized as very healthy during 2018 – 2020. Companies that were ranked very healthy were the National Pension Savings Bank Company. The Bank (BTPN) and the Bank MEGA Company. The Bank MEGA both companies reflected the company who is very healthy and able to deal with problems in the future. The performance of all companies must maintain and improve the performance of their companies ini order to overcome the problems that will occur in the future